ARI updates 2011: moving beyond numbers / Accounting Research Institute - Abu Bakar, Sahol Hamid (Accounting Research Institute (ARI), 2011)
As a national centre of excellence under the Higher Institutions’ Centre of Excellence (HICoE) initiative of the Ministry of Higher Education, the Accounting Research Institute (ARI) has been entrusted to lead research and innovation in the niche area of Islamic Financial Criminology (IFC). In essence, IFC comprises two greater research agendas: Islamic Finance & Muamalat and Financial Criminology. The first research agenda focuses on identifying issues, challenges, prospects and opportunities within the Islamic Finance industry. This is to facilitate the development of the industry and to strengthen Malaysia’s position as a global Islamic Finance hub. The second research agenda focuses on the role of Forensic Accounting and Financial Criminology as a strategic tool to mitigate and prevent financial fraud within the business environment and in particular, within the Islamic Finance industry.